2008
DOI: 10.1002/cncr.23578
|View full text |Cite
|
Sign up to set email alerts
|

Intensity‐modulated chemoradiation for treatment of stage III and IV oropharyngeal carcinoma

Abstract: BACKGROUND.Treatment outcomes for stage III and IV oropharyngeal carcinoma treated with intensity‐modulated radiotherapy (IMRT) and concurrent chemotherapy without prior surgical resection were reviewed.METHODS.Between April 2000 and September 2004, 71 patients underwent IMRT concurrent with chemotherapy without prior surgical resection for stage III and IV oropharyngeal carcinoma. Chemotherapy was platinum based. The gross tumor volume (GTV) received 70 Gy in 2.12 Gy per fraction. The high‐risk clinical tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 43 publications
(50 reference statements)
11
90
2
Order By: Relevance
“…Patients with OPC-related HPV infection have a favorable prognosis (37)(38)(39), and radiotherapy plays an important role among the treatment modalities available for these patients. The adaptation of IMRT could reduce the rate of late toxicity especially xerostomia; thus, it is considered a standard method in definitive RT for OPC (40,41). Several RCT have been conducted to demonstrate the advantages of IMRT for HNSCC patients including OPC (11,13).…”
Section: Intensity Modulated Radiotherapymentioning
confidence: 99%
“…Patients with OPC-related HPV infection have a favorable prognosis (37)(38)(39), and radiotherapy plays an important role among the treatment modalities available for these patients. The adaptation of IMRT could reduce the rate of late toxicity especially xerostomia; thus, it is considered a standard method in definitive RT for OPC (40,41). Several RCT have been conducted to demonstrate the advantages of IMRT for HNSCC patients including OPC (11,13).…”
Section: Intensity Modulated Radiotherapymentioning
confidence: 99%
“…on its pathophysiology have promoted more frequent use of new treatment modalities including the use of IMRT. We identified nine studies [3,22,[38][39][40][41][42][43][44][45] which had included patients with oropharyngeal carcinoma treated with IMRT and which had reported the incidence of osteoradionecrosis. Table 4 shows a summary of the results.…”
Section: Osteoradionecrosis (Orn)mentioning
confidence: 99%
“…It is well recognised that dental examination before treatment together with close multi-disciplinary team working with the local restorative dentist and dental hygienist will significantly reduce the risk of ORN [31]. The studies [3,22,[39][40][41][42][43][44][45] that have evaluated the reduction of ORN with IMRT in oropharyngeal cancer treatment have reported an extremely low rate of ORN with IMRT. However, the RTOG -0022 [35] study has reported a 6% ORN rate.…”
Section: Does Imrt Reduce the Risk Of Osteoradionecrosis (Orn)?mentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of linear accelerator-based intensity-modulated radiotherapy (IMRT) in improving PTV conformity [2], and normal tissue complication probability (NTCP) by sparing OAR have been well documented. Several publications have addressed the benefits of IMRT in reducing xerostomia after radiotherapy [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%